ty-5 Confers Broad-Spectrum Resistance to Geminiviruses - Yanxiang Ren; Xiaorong Tao; Dawei Li; Xiuling Yang; Xueping Zhou (Viruses, 2022)
The selection of resistant crops is an effective method for controlling geminivirus diseases. ty-5 encodes a messenger RNA surveillance factor Pelota with a single amino acid mutation (PelotaV16G), which confers effective resistance to tomato yellow leaf curl virus (TYLCV). No studies have investigated whether ty-5 confers resistance to other geminiviruses. Here, we demonstrate that the tomato ty-5 line exhibits effective resistance to various geminiviruses. It confers resistance to two representative begomoviruses, tomato yellow leaf curl China virus/tomato yellow leaf curl China betasatellite complex and tomato leaf curl Yunnan virus. The ty-5 line also exhibits partial resistance to a curtovirus beet curly top virus. Importantly, ty-5 confers resistance to TYLCV with a betasatellite. Southern blotting and quantitative polymerase chain reaction analyses showed that significantly less DNA of these geminiviruses accumulated in the ty-5 line than in the susceptible line. Moreover, knockdown of Pelota expression converted a Nicotiana benthamiana plant from a geminivirus-susceptible host to a geminivirus-resistant host. Overall, our findings suggest that ty-5 is an important resistance gene resource for crop breeding to control geminiviruses.